The genome sequence of the parsley Cheilosia, Cheilosia pagana (Meigen, 1822) [version 1; peer review: 2 approved] - Oliver Poole; Steven Falk (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Cheilosia pagana (the parsley Cheilosia; Arthropoda; Insecta; Diptera; Syrphidae). The genome sequence is 354.1 megabases in span. Most of the assembly is scaffolded into 6 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 16.76 kilobases in length.